A Comparative Analysis of Financial Performance: Family-Owned vs. Non-Family Governed Companies in the NSE - Vaid, Anuj; Gupta, Nitin (Journal of Neonatal Surgery, 2025)
This study presents a comparative analysis of the financial performance of family-owned and non-family governed companies listed on the National Stock Exchange (NSE) of India. Family-owned businesses, characterized by significant family involvement in management and ownership, often exhibit unique governance structures and strategic orientations compared to their non-family counterparts. This research aims to identify whether these distinctions translate into measurable differences in financial performance. Utilizing a dataset comprising various financial metrics over a period of five years, the study employs statistical methods to analyze profitability, liquidity, leverage, and market valuation indicators. The analysis highlights key performance differentials, assessing how family ownership influences financial outcomes. Preliminary findings suggest that family-owned firms may benefit from long-term strategic planning and robust internal controls, yet could face challenges related to nepotism and succession planning. Conversely, non-family governed firms might exhibit higher levels of professional management and diversified risk-taking. This research contributes to the broader understanding of corporate governance's impact on financial performance, offering valuable insights for investors, policymakers, and business leaders. The study underscores the need for tailored governance frameworks that enhance performance while acknowledging the inherent strengths and weaknesses of both family-owned and non-family governed firms. The findings advocate for balanced governance practices that optimize financial outcomes in diverse ownership structures.